Some Quantitative Estimates of the Possible Consequences of Armenia’s Accession to the Eurasian Economic Union - Kharatyan, Alvard; Shadyan, Aspram (Bulletin of Yerevan University G: Economics, 2015)
Within the framework of this article quantitative relationship between the main indicators characterizing the economic and trade relations of the RA were studied by means of the regression models. The possible consequences of the membership of Armenia to the Eurasian Economic Union were analyzed. The impact of the possible entry into the Eurasian Economic Union or the European Union on economic growth of Armenia was assessed.
Keywords: trade and economic relations, trade balance, economic growth, export, custom dues, integration, regression analysis, permanent and temporary effect